2015
DOI: 10.7224/1537-2073.2014-036
|View full text |Cite
|
Sign up to set email alerts
|

Dalfampridine Effects Beyond Walking Speed in Multiple Sclerosis

Abstract: Background: Dalfampridine extended release (ER) improves walking in people with multiple sclerosis (MS), as demonstrated by walking speed improvement. This exploratory study evaluated treatment effects of dalfampridine-ER on gait, balance, and walking through treatment withdrawal and reinitiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Unfortunately, no pharmacological treatment is available today for balance impairment due to MS. On the basis of its beneficial effect on information processing speed, our work hypothesis is that dalfampridine can potentially have an effect even on balance, as previously suggested [10][11][12][13]. Here, we report the findings of a substudy aimed at exploring the effect of dalfampridine versus placebo on balance in a subgroup of patients who participated in the original trial [1].…”
Section: Introductionmentioning
confidence: 87%
“…Unfortunately, no pharmacological treatment is available today for balance impairment due to MS. On the basis of its beneficial effect on information processing speed, our work hypothesis is that dalfampridine can potentially have an effect even on balance, as previously suggested [10][11][12][13]. Here, we report the findings of a substudy aimed at exploring the effect of dalfampridine versus placebo on balance in a subgroup of patients who participated in the original trial [1].…”
Section: Introductionmentioning
confidence: 87%
“…5,6 In clinical studies, a BID dose of 10-mg dalfampridine extended release (D-ER) significantly improved walking in patients with multiple sclerosis (MS) who had ambulatory difficulty. 7,8 Other exploratory MS studies have suggested that the therapeutic effects of D-ER may not be limited to walking speed but may include aspects of overall gait and balance 9,10 and possibly upper-extremity sensorimotor function. 11 In a double-blind, controlled study of patients with sensorimotor deficits that persisted for 46 months after the onset of an ischemic stroke, D-ER was well tolerated, and a significant improvement in walking speed was found in the active treatment group relative to the placebo group.…”
Section: Introductionmentioning
confidence: 99%